Deontic Modality in The Invisible Man Movie (A Systemic Functional Linguistics Perspective) - Dian Arnhy Muhtar; Neil Amstrong (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2023)
This research discusses the aspects of action and speech that are contained in The Invisible Man movie based on the theory of Jespersen and Palmer (2007) in the sub-categories commissive, directive, and volitive. The objective of this research is to describe deontic modality in three sub-categories commissive, directive, and volitive in The Invisible Man movie. This research used the descriptive qualitative method. The sources of data of this research are audio visual as primary data and written utterances from screenshotting and transcribing as secondary data. The data is from The Invisible Man movie. Data collection was carried out by searching and downloading movies, watching movies, screenshotting, classifying, and coding. Data were analyzed by presenting, describing, interpreting, and concluding data to answer research questions from this research. The results show that 18 data are included in the sub-categories commissive, directive, and volitive. Deontic modality appears because it is made by several characters in the movie that make promises and threats (commissive), make requests, order others to do something, give suggestions, carry out obligations (directive), and hope for something (volitive). The researcher found that the characters in The Invisible Man movie adopt deontic modality aspects that focus on the sub-categories commissive, directive, and volitive modality because many scenes show how aspects of the three sub-categories are used by characters to overcome existing problems. These three sub-categories are related to each other, the existence of a commissive that will lead to the directive to volitive.